PENGEMBANGAN BAHAN AJAR IPAS BERBASIS MASALAH PADA MATERI METAMORFOSIS UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV SD - BR Tarigan, Nina Enjelika; Sukmawarti, Sukmawarti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to (1) produce a problem-based science teaching material product on metamorphosis material to improve the learning outcomes of grade IV elementary school students, (2) describe the feasibility of problem-based science teaching materials on metamorphosis material in improving the learning outcomes of grade IV elementary school students, (3) describe the validity of problem-based science teaching materials on metamorphosis material in improving the learning outcomes of grade IV elementary school students. This study is a type of Research and Development (R&D) research using the ADDIE development model reference. The ADDIE model is an intrusion process consisting of five phases, namely: 1) Analysis, 2) Design, 3) Development, 4) Implementation, 5) Evaluation. The subjects in this study were expert validators of teaching materials, material experts, teacher responses and responses of grade IV B students of SDN 101808 Candirejo. The research instruments used in data collection were observation, questionnaires and documentation. The results of this study indicate that the problem-based science teaching materials on metamorphosis material to improve the learning outcomes of grade IV elementary school students are "Very Eligible" with details of the percentage of eligibility and validity given by teaching material experts of 86% with the criteria of "Very Eligible", material experts of 81% with the criteria of "Very Eligible", teacher responses of 89% with the criteria of "Very Eligible", and student responses of 97% with the criteria of "Very Eligible". And the average learning outcomes of grade IV students of SDN 101808 Candirejo increased from 48.18% to 79.27%. Therefore, it can be concluded that the Problem-Based Science Teaching Materials on Metamorphosis Material to Improve the Learning Outcomes of Grade IV Elementary School Students are "Very Eligible" used for students during the learning process.